The fast transient AT 2023clx in the nearby LINER galaxy NGC 3799 as a tidal disruption of a very low-mass star - Charalampopoulos, P.; Kotak, R.; Wevers, T.; Leloudas, G.; Kravtsov, T.; Pursiainen, M.; Ramsden, P.; Reynolds, T. M.; Aamer, A.; Anderson, J. P.; Arcavi, I.; Cai, Y. -Z.; et al. (EDP SCIENCES S A, 2025)
We present an extensive analysis of the optical and ultraviolet (UV) properties of AT 2023clx, the closest optical/UV tidal disruption event (TDE) to date (z = 0.01107), which occurred in the nucleus of the interacting low-ionization nuclear emission-line region (LINER) galaxy, NGC 3799. After correcting for the host reddening (E(B - V)(h) = 0.179 mag), we find its peak absolute g-band magnitude to be -18.03 +/- 0.07 mag, and its peak bolometric luminosity to be L-pk = (1.57 +/- 0.19)x10(43) erg s(-1). AT 2023clx displays several distinctive features: first, it rose to peak within 10.4 +/- 2.5 days, making it the fastest rising TDE to date. Our SMBH mass estimate of (M) over bar (BH) approximate to 10(6.0) M-circle dot -estimated using several standard methods- rules out the possibility of an intermediate-mass BH as the reason for the fast rise. Dense spectral follow-up reveals a blue continuum that cools slowly and broad Balmer and He II lines as well as weak He I lambda lambda 5876,6678 emission features that are typically seen in TDEs. The early, broad (width similar to 15 000 km s(-1)) profile of H alpha matches theoretical expectations from an optically thick outflow. A flat Balmer decrement (L-H alpha/L-H beta similar to 1.58) suggests that the lines are collisionally excited rather than being produced via photoionisation, in contrast to typical active galactic nuclei. A second distinctive feature, seen for the first time in TDE spectra, is a sharp, narrow emission peak at a rest wavelength of similar to 6353 angstrom. This feature is clearly visible up to 10 d post-peak; we attribute it to clumpy material preceding the bulk outflow, which manifests as a high-velocity component of H alpha (-9584 km s(-1)). Its third distinctive feature is the rapid cooling during the first similar to 20 days after peak, reflected as a break in the temperature evolution. Combining these findings, we propose a scenario for AT 2023clx involving the disruption of a very low-mass star (less than or similar to 0.1 M-circle dot) with an outflow launched in our line of sight and with disruption properties that led to efficient circularisation and prompt accretion disc formation, observed through a low-density photosphere.